2017
DOI: 10.1111/ocr.12140
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception of faces with unilateral and bilateral cleft lip and palate: An Eye‐Tracking Study

Abstract: Structured AbstractObjectives: To test the hypotheses that there are differences between orthodontists,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…Similarly, Godoy et al showed that observers spent, on average, 658 more milliseconds on a crooked nose than they did on a normal nose . Dindaroglu et al further demonstrated comparable differences in upper lip fixation when studying how laypeople gazed on photos of cleft lip patients …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Godoy et al showed that observers spent, on average, 658 more milliseconds on a crooked nose than they did on a normal nose . Dindaroglu et al further demonstrated comparable differences in upper lip fixation when studying how laypeople gazed on photos of cleft lip patients …”
Section: Discussionmentioning
confidence: 95%
“…16 Dindaroglu et al further demonstrated comparable differences in upper lip fixation when studying how laypeople gazed on photos of cleft lip patients. 34 Perhaps more telling are the social penalties suffered by those with facial deformity. For example, both patients with facial paralysis and those with crooked noses are perceived as less attractive by society, and diminished attractiveness has been strongly associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…34 We sought to better understand how parotidectomy and reconstruction of the parotidectomy facial contour deformity impacts casual observer attention using eye tracking, a well-established tool for measuring outcomes in facial plastic and reconstructive surgery. [22][23][24][25]27,30,[35][36][37][38][39][40][41][42][43] Eye tracking is a valuable tool because it allows us to objectively measure normalization in facial attention, an important measure of successful reconstruction. Casual observer attention is important because many of our daily social interactions are brief encounters with people in society (casual observers), and it is these high-volume encounters that can be a large contributor to a patient's reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Eye tracking provides an objective assessment of perception and attention toward patients with craniofacial differences. Eye tracking has been studied in coronal craniosynostosis (Linz et al, 2016) and cleft lip (Meyer-Marcotty et al, 2010; Meyer-Marcotty et al, 2011; van Schijndel et al, 2015; Dindaroglu et al, 2017; Rayson et al, 2017; Quast et al, 2018; Warne et al, 2018; Morzycki et al, 2019) as an objective method to test attention and perception through gaze patterns (Gibaldi et al, 2017). This objective assessment of attention and perception can provide insight on the social stigma of a craniofacial deformity established in the literature (Ozgur et al, 2006; Marchac et al, 2008; Singh and Moss, 2015) and how the surgery eliminates this stigma.…”
Section: Introductionmentioning
confidence: 99%